Synthesis and investigation of preformed particle gels based on acrylic monomers to reduce water cut in oil wells - Yelemessova, G.T.; Klivenko , A.N.; Orazzhanova, L.K.; Sabitova, A.N.; Shakhvorostov, A.V.; Aseyev, V.O. (Chemical Bulletin of Kazakh National University, 2026)
Oil production, which often involves the extraction of relatively large quantities of water, causes a number of environmental and mechanical problems, particularly in oil reservoirs. One way to mitigate this problem is to use polymer gels as plugging agents. This article describes a method for synthesizing acrylamide-based hydrogel particles using N,N-methylenebisacrylamide as a crosslinking agent and the addition of bentonite to prepare the hybrid composite hydrogel. FTIR spectroscopy data confirmed the formation of an acrylamide-based hydrogel. The swelling capacity of the hydrogels was studied as a function of the change in the concentration of the components contained in the composition. The swelling capacity is also estimated as a function of change in temperature, salinity and acidity of the medium. The results show that the investigated hydrogel particles exhibit remarkable swelling and have a high mechanical strength. The thermogravimetric analysis indicates stability of the hydrogel particles of up to 200℃.These particles may definitely serve as a robust sealant. They show high resistance to heat and salt exposure as well as stability in acidic and alkaline conditions. Considering physicochemical properties discussed in this paper, hydrogel particles can be utilized as a cost-effective potting agent.